Engagement and role of surgical trainees in global surgery: Consensus statement and recommendations from the Association of Surgeons in Training. (April 2018) - Mohan, Helen M.; Fitzgerald, Edward; Gokani, Vimal; Sutton, Paul; Harries, Rhiannon; Bethune, Robert; McDermott, Frank D.; ,
Abstract: Background: There is a wide chasm in access to essential and emergency surgery between high and low/middle income countries (LMICs). Surgeons worldwide are integral to solutions needed to address this imbalance. Involving surgical trainees, who represent the future of surgery, is vital to this endeavour. The Association of Surgeons in Training (ASiT) is an independent charity that support surgical trainees of all ten surgical specialties in the UK and Ireland. ASiT convened a consensus meeting at the ASiT conference in Liverpool 2016 to discuss trainee engagement with global surgery, including potential barriers and solutions. Methods: A face-to-face consensus meeting reviewed the engagement of, and roles for, surgical trainees in global surgery at the ASiT Conference (Liverpool, England), March 2016. Participants self-identified based on experience and interest in the field, and included trainees (residents and students) and consultants (attending grade). Following expert review, seven pre-determined core areas were presented for review and debate. Extensive discussion was facilitated by a consultant and a senior surgical trainee, with expertise in global surgery. The draft derived from these initial discussions was circulated to all those who had participated, and an iterative process of revision was undertaken until a final consensus and recommendations were reached. Results: There is increasing interest from trainee surgeons to work in LMICs. There are however, ethical considerations, and it is important that trainees working in LMICs undertake work appropriate to their training stage and competencies. Visiting surgeons must consider the requirements of the hosting centres rather than just their own objectives. If appropriately organised, both short and long-term visits, can enable development of transferable clinical, organisational, research and education skills. A central repository of information on global surgery would be useful to trainees, to complement existing resources. Challenges to trainees considering a global surgery placement include approval for placements while on a training program, financial cost and dangers inherent in working in a resource poor setting. Currently global surgery experience is generally as an out of program experience and does not count for certificate of completion of training (CCT). Methods to recognise surgical trainee global surgery experience as an integrated part of training should be explored, similar to that seen in other specialties. Conclusion: There is a role for surgical trainees to become involved in Global Surgery, especially in partnership with local surgeons and with appropriate ethical consideration. Trainees develop translational skills in resource poor settings. Development of appropriate pathways for recognition of global surgery experience for CCT should be considered.